Aesthetics of resistance and the documentary (document 03): Tha Rainbow House Women - Sobrinho, Gilberto Alexandre (Faculdade de Educação/Universidade Estadual de Campinas, 2021)
In the “Trilogia Afro-Campineira” there are three documentary achievements, in which I directed, scripted and produced the films. There are three short films focused on protagonists of cultural, religious and artistic processes, all defenders of manifestations of African matrixes and their powerful hybridisms, located in the metropolitan region of Campinas-SP (RMC). The films are Diário de Exus (2015), A Dança da Amizade, Histórias de  Urucungos, Puítas and Quijengues (2016) and A Mulher da Casa do Arco-Íris (2017/2018). In films, what I call the “aesthetics of resistance” are developed, prioritizing Afro-diasporic narratives, in a creative process in which aesthetics and politics converge. Aesthetically, the documentary brings together the processes of observation, participation (interview), performance and “poetry”, in a set of images and sounds centered on people and spaces that are organized communally around Afro-centred codes. Politically, the role of culture and religion in the affirmation and construction of identity of the black people in Brazil is highlighted, which deepens the understanding of the role of culture in the resistance of a people. This text documents the process of making the third short film in the trilogy, A Mulher da Casa do Arco-iris.